Differential Effect of β‐Blockers for Heart Rate Control in Coronary Artery Disease - Cordero, Alberto (Clin Cardiol, 2011)
BACKGROUND: Resting heart rate is an independent risk factor for cardiovascular disease and is mainly controlled by β‐blockers (BBs). BBs are part of the optimal medical treatment for coronary artery disease (CAD), and their benefit correlates with resting heart rate (RHR) reduction. HYPOTHESIS: RHR is poorly controlled in daily practice among patients with stable cardiovascular disease, and control is only achieved by some BBs. METHODS: Observational, cross‐sectional, and multicenter study of CAD patients recruited nationwide from 20 institutions. Antecedents, risk factors, and treatments were collected. Controlled RHR was considered at <70 bpm. RESULTS: The mean age of the 2897 patients included was 67.4 years (11.4%), and 75.9% were males. Patients treated with a BB (56.5%) had a lower mean age and comorbidities. The mean RHR was 69.6 bpm (12.6). A significantly lower RHR was observed in patients treated with a BB compared to the rest (67.2 vs 73.0 bpm; P<0.01), and no difference was observed in patients treated with a calciumchannel blocker (CCB). The analysis by individual agents identified that only patients treated with atenolol, bisoprolol, and metoprolol had significantly lower RHR than those not receiving a BB. No differences were observed in mean doses of each agent according to RHR control, except for verapamil. BB treatment was independently associated with RHR control (odds ratio [OR]: 2.42, 95% CI: 2.05–2.87; P<0.01), and no association was found for nondihydropyridine CCBs (OR: 0.99, 95% CI: 0.96–1.02; P = 0.38). Bisoprolol (OR: 1.56, 95% CI: 1.38–1.78; P<0.01), atenolol (OR: 2.01, 95% CI: 1.57–3.49; P<0.01), and metoprolol (OR: 1.29, 95% CI: 1.04–1618; P = 0.04) were independently associated with RHR control. CONCLUSIONS: RHR is poorly controlled in CAD patients, and although BBs are the most efficient therapy, in daily clinical practice RHR <70 bpm is only independently associated with atenolol, bisoprolol, or metoprolol. © 2011 Wiley Periodicals, Inc. The TRECE registry has an unrestricted grant from Servier Laboratories, Spain. The authors have no other funding, financial relationships, or conflicts of interest to disclose.